Skin and Scars: Probing the Visual Culture of Addiction. (June 2018) - Skelly, Julia
What does considering skin carefully and specifically illuminate about addiction, addiction discourse and/or the visual culture of addiction, that more general considerations of the body do not? What light is shed when we talk about skin and addiction? I want to propose in this brief article that in looking at addiction and addiction discourse through the lens of skin studies, we see with even more clarity the thinness of the argument that addiction is legible from corporeal evidence. I conclude that while we may want skin to tell us things about others, it nevertheless behooves us to be wary of what we think skin tells us about addiction.